Grasshopper magic - Jonell, Lynne (Jonell, Lynne. Magical mix-ups, 2013)
To prove he is brave enough to portray his ancestor in a town parade, Abner Willow eats a bowlful of fried grasshoppers and suddenly gains the magical ability to leap and jump.